2019
DOI: 10.1055/s-0039-1697671
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Umbilical Cord Clamping is Not Associated with Acute Kidney Injury in Very Low Birth Weight Neonates

Abstract: Objective This study aimed to determine if delayed cord clamping (DCC) is associated with a reduction in neonatal acute kidney injury (AKI). Study Design A retrospective single-center cohort study of 278 very low birth weight (VLBW) neonates was performed to compare the incidence of AKI in the following groups: immediate cord clamping (ICC), DCC, and umbilical cord milking. AKI was diagnosed by the modified neonatal Kidney Diseases and Improving Global Outcomes (KDIGO) definition. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Our ndings are consistent with previously published data. [20] There are a few potential explanations for our ndings. First, in a separate evaluation of this same cohort, it was found that correcting sCr for uid balance uncovered numerous missed episodes of AKI in the cohort.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our ndings are consistent with previously published data. [20] There are a few potential explanations for our ndings. First, in a separate evaluation of this same cohort, it was found that correcting sCr for uid balance uncovered numerous missed episodes of AKI in the cohort.…”
Section: Discussionmentioning
confidence: 94%
“…[19] A retrospective single-center cohort study of 278 very low birth weight neonates found no differences in acute kidney injury (AKI) by cord management strategy and no studies have compared two year kidney outcomes by cord management strategy. [20] Our objective was to evaluate the association of different cord management strategies with AKI and twoyear kidney outcomes in ELGANs. We hypothesized that in ELGANs, DCC would be associated with decreased in-hospital AKI and improved two-year kidney outcomes compared to ECC.…”
Section: Introductionmentioning
confidence: 99%